2021
DOI: 10.1155/2021/6706218
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Pneumonia in an Adolescent Patient with Allergic Asthma

Abstract: Background. The latest coronavirus infection due to SARS-CoV-2, which started in China in December 2019, was announced as a pandemic by the World Health Organization (WHO) in March 2020. All epidemiological data so far show us that SARS-CoV-2 infection is less serious in children than in adults. Allergic asthma, the most common chronic disease in children, is usually not to be related to greater risk or severity for COVID-19 in pediatric populations. Although reports/research on asthma and COVID-19 in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The current study findings are similar to COVID-19 disease classification in other studies wherein patients can present in mild, moderate and severe-to-critical states [ 45 , 46 ]. Brinton et al reported mortality amongst bronchial asthma patients who received corticosteroids while presenting with pneumonia [ 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…The current study findings are similar to COVID-19 disease classification in other studies wherein patients can present in mild, moderate and severe-to-critical states [ 45 , 46 ]. Brinton et al reported mortality amongst bronchial asthma patients who received corticosteroids while presenting with pneumonia [ 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…T-helper 2 polarization might impair the efficient antiviral immune response [9,10]. Asthmatic patients also have a greater susceptibility to respiratory viral infections, which may be a trigger for exacerbations [11,12]. It is critically important to keep the disease under control in asthma patients [13,14].…”
Section: Asthmamentioning
confidence: 99%
“…There was an increase in the frequency of admission to hospital with urticaria. There are many cases of urticaria associated with COVID-19 in the literature [12]. This situation should not be overlooked before the patient is evaluated as urticaria and treatment are started.…”
Section: Urticaria-angioedemamentioning
confidence: 99%